LATAR BELAKANG DAN BERKEMBANGNYA DIKOTOMI ANTARA ILMU DAN AGAMA DALAM ISLAM - Muhairira, Nurjamilatul; Sudirman (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2024)
Dichotomy between Islam and religionIn Islam, since the beginning of Islam emphasized the importance of seeking knowledge, viewing both as a path to a better understanding of God and the universe, but often over time, there has been a debate about the relationship between modern science and Islamic teachings. This research aims to find out when and what causes the dichotomy between science and religion. This research uses a literature study method by exploring sources related to the background of the dichotomy between science and religion in Islam. The results show that in Islam itself there is no scientific dictytomy. And the separation between science and religion occurred in the Middle Ages, precisely in the 11th century AD, or also called the golden age where the peak occurred in the abbasid state. It's just that in this time there are scientists who are more inclined or more in-depth in knowledge according to their respective abilities. And it is also explained in the Qur'an that science and religion must be well integrated with each other. Keywords: Background and Development, Dichotomy, Science and Religion